Examining Scotland’s sentencing landscape through administrative data - Morales-Gomez, Ana; Mcvie, Susan (International Journal of Population Data Science, 2026)
Sentencing is one of the most critical stages in the criminal justice process. Understanding who is being convicted and for what helps us to understand the offender population and provides the evidence needed to support informed decisions around criminal justice policy. It is also essential for assessing both fairness and consistency. Despite its importance, systematic evidence on how sentences are distributed across offender groups and offence types remains limited in Scotland. This research presents an initial exploration of the Scottish Offender Index, a newly available administrative dataset covering the offender population in Scotland from 1997 to 2021. The study examines broad patterns in sentencing and offender characteristics over time. The longitudinal and population-level nature of the data allows us to describe the evolving composition of the offender population, the distribution of sentencing outcomes, and how these patterns differ across key demographic and offence categories. This study shows how large-scale administrative data can strengthen our understanding of how the criminal justice system operates in practice. By analysing long term changes in sentencing and the convicted population, our finding highlights how social changes and legal reforms influence justice outcomes over time. The implications of these findings for policy, practice and those affected by sentencing decisions will also be discussed.